Red Ties and Residential Schools : Indigenous Siberians in a Post-Soviet State - Bloch, Alexia (Book collections on Project MUSE., 2004)
""This thoughtful study should interest anyone concerned with social and political life at the periphery of today's Russian Federation.""--Choice.